Application of the Demonstration Method to Improve Students' Ability to Describe the Occurrence of Solar Eclipses and Lunar Eclipses - Euis Waliyati (Indonesian Journal of Educational Science and Technology, 2023)
Natural Science (IPA) deals with how to systematically find out about nature. This research was carried out in three cycles of learning actions, each cycle consisting of planning, implementing, observing and reflecting by applying scientific work observing, recording observed data, interpreting observed data, classifying, predicting, communicating, reporting and concluding. The learning actions of this cycle are focused on increasing students' ability to describe the occurrence of a solar eclipse, cycle 2's learning actions are focused on increasing students' ability to describe the occurrence of a lunar eclipse, and cycle 3's actions are focused on improving students' abilities to describe the Christian and Islamic calendars. The purpose of this study was to improve teacher performance in planning and implementing the demonstration method in cooperative learning, increasing students' scientific work activities, and improving students' learning outcomes in describing the occurrence of a lunar eclipse. The results showed an increase in teacher performance in planning learning cycle 1 achieved an average value of 68.25%, cycle 2 achieved 78.50% and cycle 3 achieved an average value of 100%.